2018
DOI: 10.1111/bjd.16336
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of phototherapy, adalimumab and betamethasone-calcipotriol on effector and regulatory T cells in psoriasis

Abstract: The differential effects reported here for the above-mentioned treatment modalities could be exploited to optimize or design therapeutic strategies to overcome the inflammatory drivers more effectively and restore the Th17-Treg balance in psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
(45 reference statements)
0
9
0
1
Order By: Relevance
“…It was recently reported that Cal-BDP combination therapy increases CD4 + CD25 + Foxp3 + CD127 lo Tregs and reduces Th17 cells in the blood and skin lesions of patients with psoriasis, suggesting that Cal-BDP combination therapy restores the Treg-T17 balance 5 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently reported that Cal-BDP combination therapy increases CD4 + CD25 + Foxp3 + CD127 lo Tregs and reduces Th17 cells in the blood and skin lesions of patients with psoriasis, suggesting that Cal-BDP combination therapy restores the Treg-T17 balance 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have suggested that an imbalance between regulatory CD4 + CD25 + Foxp3 + T cells (CD4 + Tregs) and Th17 cells is important in the pathogenesis of psoriasis 5 , while CD4 + Treg dysfunction has also been detected in this disease 6 . Other regulatory cell subsets have been described, such as regulatory CD8 + CD122 + T cells (CD8 + Tregs) 7,8 , and regulatory CD1d + CD5 + IL-10 + B cells (Bregs) also exist 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Treg cells from psoriasis are defective in the Akt-FOXO1 signaling pathway [42]. Dysfunctional or reduced Treg cells have been described in peripheral blood and in psoriatic lesional skin in patients [43][44][45]. The relevance of local Treg cells in skin inflammation has been recently reported, where using the imiquimod-induced murine model of psoriasis demonstrated that Treg cells limit the exacerbation of local skin inflammation and initiate also disease remission [46].…”
Section: Discussionmentioning
confidence: 99%
“…38 Interestingly, Kotb et al also showed that the density of Tregs increases during UVA treatment or topical application of D vitamin and betamethasone. 38 In contrast, Keijsers et al observed a decrease in Tregs analysed by IHC staining in 12 psoriasis patients treated with topical application of D vitamin and betamethasone, although with a high interindividual variation. 39 In this latter article, the skin of patients treated with the TNF blocker adalimumab, however, exhibits an increased Foxp3/CD4 ratio after treatment compared to before treatment, in line with Kotb et al These studies did not present epidermal and dermal data separately but Tregs likely persist in the dermis, as FOXP3 expression in CD4 + T cells from resolved epidermis after both UVB and biologics treatment is not significantly different from healthy skin.…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…On a cellular level, the density of pathogenic T cells remaining in the tissue may play a role, but several studies indicated that homoeostasis is maintained by tolerogenic cells within the tissue. The proportion of regulatory T cells (Tregs) among CD4 + T cells is lower in both lesional and non‐lesional skin compared to levels in healthy skin 38 . Interestingly, Kotb et al also showed that the density of Tregs increases during UVA treatment or topical application of D vitamin and betamethasone 38 .…”
Section: The Cellular Components Of Local Memories In the Skinmentioning
confidence: 99%